PENEGAKAN PRINSIP SPECIAL AND DIFFERENTIAL TREATMENT DALAM PERSEPEKTIF HUKUM PERDAGANGAN INTERNASIONAL - Hendra Djaja (Jurnal Cakrawala Hukum, 2017)
In the International Commerce law system, there were some common principles of free market implementation.Besides the common principles, GATT law system also had dealt to receive another principle that was morespecific that deviated the common principles. This exception principle was called Special and DifferentialTreatment Principles or SD principles. The purpose of SD was to help the developing countries or underdevelopedcountriesto get benefit in doing the commerce to the developed industrial countries by havingspecial treatment which was different from the common principles and which were many times broken bydeveloped industrial countries, so it was felt as an unfair treatment by developing countries.